SV 12 Kingston Harbour. St. Vincent. W. I. - (:unkn) unknown (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2022)
This photo shows the landscape of Kingston (Kingstown), St. Vincent with forest covered hills in the background Info. At the back: SV12 Kingston Harbour, St. Vincent W.I. £6 Published by Wayfarer Bookstore, St. Vincent, West Indies. Printed in ENGLAND by PHOTO PRECISION LTD.
Kingston Harbour, St. Vincent, W.I.
Landscape, colour, 4 x 6 in.
Keywords: Landscape; Buildings; Harbors; Cityscapes; Cities and towns; Boats; Wayfarer Bookstore; Photo Precision Limited